Effect of microbes on Patterns of Labeled White Blood Cells in Osteomyelitis (Indian Journal of Public Health Research & Development, 2023)
Aim: This study investigates the effect of microbiological characteristics of causative organisms on the scintigraphicpatterns of labelledwhite blood cell (WBC) scans in cases of proven osteomyelitis.Methods: Retrospective analysis of 25 patients referred with suspected osteomyelitis and had both bone andlabelled WBC scans performed and complete records of the microbiological culture of the causative organism.The bone and labelled WBC scans were retrieved and reviewed by two nuclear medicine physicians. Any definitefocal accumulation of labelled WBCs within the bone was considered positive for osteomyelitis. Diagnosis ofosteomyelitis in the discharge summary was considered the reference standard and was based on a combinationof the clinical scenario, imaging, and laboratory findings including microbiology. A correlation of the pattern oflabelled WBC and the type of microorganisms was done.Results: A total of 16 patients were included in this study, seven females and nine males. Of these, seven patientshad Gram-positive whereas nine patients had Gram-negative organisms. The majority (85.7%) of Gram-positiveorganisms showed increased accumulation of labelled WBCs, whereas only one-third (33.3%) of patients withGram-negative organisms had such findings.Conclusion: The pattern observed in this study shows that the falsenegative results of labelledWBC scanswere mainly noted in patients with Gram-negative as opposed to Gram-positive infections. This confirms theexperimental animal study findings that the secretion of anti-chemotactic factors by Gram-negative organisms,seems to be inhibiting the migration of labelled WBCs to the site of infection. The inhabitation is decreasing theaccumulation of labelled WBCs and consequently resulting in a falsenegative finding. The study adds to evidencethat microbiological characteristics of the causative organisms are another explanation for the falsenegative WBCin proven osteomyelitis.
Keywords: Bone scan, Gram-negative bacteria, Gram-positive bacteria, labelled white blood cells, osteomyelitis.